Cognitive Behavioral Therapy for Insomnia Enhances Depression Outcome in Patients with Comorbid Major Depressive Disorder and Insomnia - Manber, Rachel (Associated Professional Sleep Societies, LLC, 2008)
STUDY OBJECTIVE: Insomnia impacts the course of major depressive disorder (MDD), hinders response to treatment, and increases risk for depressive relapse. This study is an initial evaluation of adding cognitive behavioral therapy for insomnia (CBTI) to the antidepressant medication escitalopram (EsCIT) in individuals with both disorders. DESIGN AND SETTING: A randomized, controlled, pilot study in a single academic medical center. PARTICIPANTS: 30 individuals (61% female, mean age 35±18) with MDD and insomnia. INTERVENTIONS: EsCIT and 7 individual therapy sessions of CBTI or CTRL (quasi-desensitization). MEASUREMENTS AND RESULTS: Depression was assessed with the HRSD(17) and the depression portion of the SCID, administered by raters masked to treatment assignment, at baseline and after 2, 4, 6, 8, and 12 weeks of treatment. The primary outcome was remission of MDD at study exit, which required both an HRSD(17) score ≤ 7 and absence of the 2 core symptoms of MDD. Sleep was assessed with the insomnia severity index (ISI), daily sleep diaries, and actigraphy. EsCIT + CBTI resulted in a higher rate of remission of depression (61.5%) than EsCIT + CTRL (33.3%). EsCIT + CBTI was also associated with a greater remission from insomnia (50.0%) than EsCIT + CTRL (7.7%) and larger improvement in all diary and actigraphy measures of sleep, except for total sleep time. CONCLUSION: This pilot study provides evidence that augmenting an antidepressant medication with a brief, symptom focused, cognitive-behavioral therapy for insomnia is promising for individuals with MDD and comorbid insomnia in terms of alleviating both depression and insomnia. CITATION: Manber R; Edinger JD; Gress JL; San Pedro-Salcedo MG; Kuo TF; Kalista T. Cognitive behavioral therapy for insomnia enhances depression outcome in patients with comorbid major depressive disorder and insomnia. SLEEP 2008;31(4):489-495.